HEAD UP POSITION 30° - 45° FOR SUCCESSFUL VENTILATOR WEANING PROCESS IN INTENSIVE CARE UNIT - Wibowo, Nugroho Ari; Priyantini, Diah; Saputro, Suyatno Hadi; Kartikaratri, Erinda Sari; Ayatulloh, Daviq (Journal of Vocational Nursing, 2025)
Introduction: Ventilator weaning is the process of transitioning a patient from ventilator support to independent breathing for more than 48 hours. A 30°-45°head-up position, where the patient's head is raised above the bed, with the body parallel to the bed and the legs straight or unflexed, is believed to influence the success of the weaning process. This study aims to analyze the relationship between a 30°-45°head-up position and the success of ventilator weaning. Methods: A retrospective design was used, with 40 patients meeting the inclusion and exclusion criteria. Total sampling was applied, taking the entire population as the sample. Data were collected from patient medical records in the ICU from May to July 2023 to evaluate the head-up position and the success of ventilator weaning. Data analysis was performed using the chi-square test to determine the significance of the relationship between the variables. Results: The study results showed a significant association between a 30°-45° head-up position and successful weaning in ventilator patients, with a p-value of 0.000 (<0.05). The majority of patients positioned with their heads up were successfully extubated and did not require further ventilator support for the next 48 hours. This head-up position is believed to help increase lung capacity and respiratory efficiency during the weaning process. Conclusions: maintaining a 30°-45° head-up position playe a crucial role in successful ventilator weaning. Therefore, careful monitoring and thorough assessment during the weaning process could be essential to ensure rapid and accurate extubation in ventilator patients.